High-strength wear-resistant sliding rail prefabricated part as well as preparation method and application thereof

By using prefabricated slide rails composed of materials such as multi-grade particle size mullite and alumina powder, the existing slide rail materials are easily deformed, oxidized and worn in high-temperature environments, and the high-temperature strength, corrosion resistance and thermal shock resistance of the slide rails are significantly improved.

CN119930307AActive Publication Date: 2025-05-06HUBEI ANNAIJIE FURNACE LINING MATERIAL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510430724.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-08
Publication Date
2025-05-06
Estimated Expiration
2045-04-08

AI Technical Summary

Technical Problem

The existing heating furnace rail materials are prone to deformation, oxidation and wear in high temperature environments, resulting in short service life, high maintenance costs, and insufficient surface wear resistance.

Method used

A high-strength wear-resistant sliding rail prefabricated parts consisting of mullite, alumina powder, calcium aluminate cement, silicon micropowder, alumina hollow spheres and water reducer are used to form a continuous ceramic network through mutual filling and high-temperature reaction between multiple levels of particle size to improve the high-temperature strength, corrosion resistance and thermal shock resistance of the material.

Benefits of technology

It significantly improves the service life of the slide rail, enhances high temperature strength, corrosion resistance and thermal shock resistance, and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of green special refractory ceramics, in particular to a high-strength wear-resistant sliding rail prefabricated part and a preparation method and application thereof. The sliding rail prefabricated part is prepared from the following raw material components in percentage by weight: 39.5 to 90 percent of mullite particles, 3.3 to 10 percent of alumina powder, 2.4 to 10 percent of calcium aluminate cement, 2.4 to 10 percent of silica powder, 0 to 30 percent of alumina hollow spheres and 0.1 to 0.5 percent of a water reducing agent, the mullite is prepared from the following grain fractions: 10-30% of 5-8 mm; 10 to 40 percent of 3 to 5 mm; 10 to 30 percent of 1 to 3 mm; 0 to 70 percent of 0 to 1 mm; the alumina powder is formed by mixing calcined alumina powder with the particle size d50 of 4-6m, activated alumina powder with the particle size d50 of 1-2m and trehalose composite alpha-alumina powder with the particle size d50 of 8-10m. The sliding rail prefabricated part is excellent in high-temperature strength, corrosion resistance and thermal shock resistance, and the service life of the sliding rail is remarkably prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of green special refractory ceramics, and more specifically, to a high-strength wear-resistant slide rail prefabricated part and a preparation method and application thereof. Background Art

[0002] Industrial heating is an important part of the manufacturing industry, and industrial furnaces are important equipment for industrial heating, which develops in tandem with the development of industry. There are many types of industrial furnace equipment, which are widely used in various industries and have a wide impact. Among them, the forging heating furnace is one of the important equipment in the metal processing industry, mainly used for heating metal materials. During the forging process, the temperature in the furnace is about 800℃-1250℃, the heating rate is 100℃ / min, and the furnace temperature fluctuates greatly. The heating furnace slide rail, as the bearing and guiding part, bears the sliding effect of the steel billet in a high temperature environment.

[0003] Heating furnace slide rail bricks are usually made of refractory bricks, refractory castables or other high-temperature refractory materials. They have good wear resistance, high temperature resistance and chemical corrosion resistance. They can be used as sliding supports and thermal insulation layers to be better applied in heating equipment (such as industrial furnaces and hearths). However, many current slide rail prefabricated parts used in heating furnaces still face many technical difficulties, such as: poor high temperature resistance: existing slide rail materials are mostly made of conventional alloy steel or carbon steel, which are prone to deformation, oxidation and wear under long-term high temperatures, resulting in slide rail failure and increased maintenance costs; short replacement cycle: traditional slide rails are damaged by friction and high temperature during use, and often need to be replaced frequently, affecting production efficiency; insufficient surface wear resistance: the surface of the slide rail is in direct contact with the metal workpiece, which is very prone to wear and corrosion. Summary of the invention

[0004] In order to solve at least one of the above technical problems, the present invention provides a high-strength and wear-resistant slide rail prefabricated component and its preparation method and application, which enables the slide rail prefabricated component to have excellent high-temperature strength, corrosion resistance and thermal shock resistance by selecting reasonable casting material raw materials and the content of each component, thereby significantly improving the service life of the slide rail.

[0005] In a first aspect, the present invention provides a high-strength wear-resistant slide rail prefabricated component, comprising the following raw material components by weight percentage: 39.5-90% of mullite particles, 3.3-10% of alumina powder, 2.4-10% of calcium aluminate cement, 2.4-10% of silica powder, 0-30% of alumina hollow spheres, and 0.1-0.5% of a water reducer; The mullite is composed of the following particle sizes, and the particle size and weight percentage of each particle size in the mullite are: 5-8mm 10-30%; 3-5mm 10-40%; 1-3mm 10-30%; 0-1mm 0-70%; The alumina powder has a particle size of d50 Calcined alumina powder with a particle size of 4-6µm 50 Activated alumina powder with a particle size of 1-2µm 50 It is a mixture of 8-10µm trehalose composite α-alumina powder.

[0006] The slide rail prefabricated part of the present invention uses mullite as the main aggregate, which has a high melting point (about 1850°C) and load softening temperature, excellent oxidation resistance, acid and alkali corrosion resistance and high temperature creep resistance, small deformation under load, and low thermal expansion coefficient (5.3x10 -6 K), thereby making the slide rail preform have excellent thermal shock resistance.

[0007] Among them, the present invention adopts four particle size ranges of mullite, each accounting for a certain proportion, to achieve multi-level particle size mutual filling (large particles form the skeleton, and small particles fill the gaps). Specifically, large particles (5-8mm) are used to form a crack deflection structure to slow down the crack propagation rate, and medium particles (1-5mm) are used to improve the fracture toughness through the interface locking effect; finally, fine particles (0-1mm) are used to fill the pores to limit stress concentration under thermal shock, effectively reducing the sintering shrinkage rate of the product.

[0008] On the basis of the above-mentioned multi-grade granularity mullite, the present invention further adds a set amount of alumina powder, calcium aluminate cement, silica powder, alumina hollow spheres and a water reducing agent. Among them, alumina powder can fill the pores between mullite particles and form a high-purity alumina crystal phase, thereby improving the refractoriness (>1700℃) and resistance to slag erosion. Calcium aluminate cement, as a binder, can be hydrated at room temperature to form a hydrated calcium aluminate binding phase to provide initial strength, and generate a calcium aluminate ceramic phase after high-temperature dehydration to avoid excessive shrinkage and cracking. Silica powder is nano-scale SiO2. On the one hand, it can be combined with Al2O3 to fill the micropores between mullite particles, and on the other hand, it can react with Al2O3 at high temperature to generate mullite, further improving the compactness and hot strength of the slide rail prefabricated parts. Alumina hollow spheres can reduce thermal conductivity (can be <1.0 W / m·K) and reduce density (can be <1.5g / cm³) through spherical pores. Finally, a set amount of water reducer is used to disperse the particles through electrostatic repulsion, reduce the water-cement ratio (improve workability), and reduce drying shrinkage and cracking.

[0009] In addition, the present invention further defines the composition of alumina powder, which is based on the high stability of calcined alumina, which is suitable for high temperature environment; the large surface area of ​​activated alumina has better reaction activity; and the organic component trehalose is introduced into trehalose composite α-alumina, which can affect the sintering behavior and material properties to a certain extent. In addition, since the difference in particle size will affect the packing density and the arrangement of particles during the sintering process, the present invention also performs gradient control on the particle size of alumina powder, in which the large-particle 8-10µm trehalose composite α-alumina is used as the main skeleton, the 4-6µm calcined alumina is used as the relay support, and finally the gap is filled with 1-2µm activated alumina, thereby greatly improving the density of the slide rail preform.

[0010] Therefore, the slide rail prefabricated component obtained by the present invention has excellent high-temperature strength, corrosion resistance and thermal shock resistance, and can significantly improve the service life of the slide rail.

[0011] Preferably, the weight ratio of the calcined alumina powder, the activated alumina powder and the trehalose composite α-alumina powder is 1-6:3-9:85-96.

[0012] By adopting the above technical scheme, the alumina powder of the present invention is mainly composed of trehalose composite α-alumina powder. This is based on the fact that when preparing the slide rail preform, water is usually added to mix the components. At this time, the trehalose in the trehalose composite α-alumina powder dissolves in water, which can improve the fluidity of each component and make the slide rail preform easier to form; in the molding stage of the slide rail preform, the dissolved trehalose can further fill the gaps between the ceramic particles and crystallize, thereby enhancing the bonding force between the particles, thereby effectively increasing the strength and stability of the slide rail preform; in the sintering stage of the slide rail preform, the trehalose is dehydrated and carbonized at high temperature, and then converted into amorphous carbon with a graphene-like structure, thereby effectively improving the toughness and wear resistance of the slide rail preform; in addition, the carbon generated by it will also react with the alumina in the component at high temperature to form aluminum-carbon compounds and react with silicon dioxide to form silicon carbide. These reactions will further enhance the mechanical properties and thermal stability of the ceramic. Therefore, in the whole process, trehalose not only acts as a plasticizer and binder, but is also converted into functional carbon material in the subsequent high-temperature treatment, which not only changes the microstructure of the slide rail preform, but also gives the slide rail preform better high temperature resistance and thermal shock resistance.

[0013] In addition, compared with the method of adding trehalose alone, the present invention can obtain a slide rail preform with better thermal shock resistance in a composite state; this may be because the composite process allows the trehalose to coat the surface of the α-alumina particles in a molecular layer, avoiding excessive local concentration due to agglomeration when directly added, thereby improving the uniformity and performance of the material; secondly, trehalose will decompose or volatilize during sintering during high-temperature treatment, and pre-compounding trehalose with α-alumina can better achieve interfacial bonding to form a uniform porous structure; thirdly, the starting temperature of thermal decomposition of trehalose after compounding is increased from 160°C to 300°C, avoiding premature decomposition in the mixing or drying stage that may lead to process loss of control.

[0014] Preferably, the preparation method of the trehalose composite α-alumina powder comprises the following steps: Mix α-alumina powder and trehalose solution to make slurry, inject the slurry into a mold, vibrate and exhaust, place it in an environment with a humidity of 80-100% and a temperature of 30-40°C for curing for 24-48 hours, and place it at 100-150°C for low-temperature pre-sintering after demoulding, remove moisture and then grind it.

[0015] The present invention adopts the method of vibration exhaust + mold forming, which helps to make the slurry more compact, and combined with high humidity curing (80-100% RH), the trehalose hydrogen bond network mediated by water molecules penetrates the surface pores of α-alumina to form a chemical adsorption layer, which can effectively reduce the problem of physical adhesion and easy falling off of mechanical mixing; on this basis, the present invention further limits the pre-firing temperature to 100-150, which is lower than the decomposition threshold of trehalose (160°C), thereby retaining its carbon precursor function, and compared with the traditional high-temperature sintering (>500°C) process, it can reduce the contamination of the pyrolysis products to the alumina lattice; the above steps are independently controllable and the steps are simple and convenient, which are suitable for large-scale production.

[0016] Preferably, the weight ratio of the α-alumina powder to trehalose is 3:1.

[0017] By adopting the above technical scheme, a 25% (3:1) trehalose content can not only form an effective coating layer to enhance the interfacial bonding strength, but also avoid excessive introduction leading to excessive porosity after high-temperature carbonization, and ensure that the trehalose solution fully infiltrates the surface of the α-alumina powder to prevent local agglomeration; in addition, when the trehalose content is ≤25%, the contamination of the α-alumina lattice by its thermal decomposition residue is controllable (residual carbon content <1.5%), thereby ensuring the process stability in the pre-firing stage (100-150°C).

[0018] Preferably, the alumina content in the aluminate cement is 65-70%, and the calcium oxide content is 29-33%.

[0019] By adopting the above technical solution, the high content of alumina (65-70%) can give aluminate cement excellent refractory properties (refractory can reach above 1600°C), so that it can still maintain structural stability at high temperatures, not easy to soften or melt, and also has strong resistance to corrosion by chemical media such as sulfates and weak acids, thereby further improving the corrosion resistance and high temperature strength of the slide rail prefabricated parts. In addition, the present invention, with the combination of the above-mentioned specific alumina powder, can improve the late shrinkage or micro-expansion of aluminate cement caused by high calcium content (29-33% CaO), thereby effectively reducing the risk of cracking in a dry environment.

[0020] Preferably, the purity of the hollow alumina spheres is ≥99%, the particle size is 0.2-0.5 mm, and the bulk density is 0.8-0.9 g / cm 3 .

[0021] By adopting the above technical scheme, the alumina hollow spheres have a low impurity content, a relatively concentrated particle size, and good fluidity, which is convenient for filling molds or preparing uniform composite materials; the hollow structure has low thermal conductivity, which can reduce the solid-phase heat transfer path, relieve thermal stress, reduce the risk of cracking under sudden high temperature changes, and can also reduce the overall weight of the material to a certain extent.

[0022] Preferably, the water reducing agent is at least one of sodium tripolyphosphate, sodium hexametaphosphate and boric acid.

[0023] Using the above technical solution, sodium tripolyphosphate and sodium hexametaphosphate are both condensed phosphates, which can disperse cement particles through an adsorption-desorption mechanism. The weak acidity of boric acid can adjust the pH value of the slurry (pH 7.5-8.5), alleviating the excessive delay of cement coagulation in the phosphate alkaline environment. Therefore, the appropriate water reducer can be selected according to the needs of different alkaline water systems.

[0024] In a second aspect, the present invention provides a method for preparing the above-mentioned high-strength wear-resistant slide rail prefabricated part, comprising the following steps: Take a set amount of raw material components, add 4.5-5.5% of water accounting for the total weight of the raw material components to mix, stir and vibrate to form, cure for 20-30 hours at a temperature of 20-50°C and a relative humidity of 80-100%, heat to 110-115°C at 10-20°C / h after demolding, keep warm for 24-48 hours, then heat to 350°C at 15-30°C / h, keep warm for 24-48 hours, finally heat to 600°C at 15-20°C / h, keep warm for 16-32 hours, and obtain the high-strength wear-resistant slide rail prefabricated component.

[0025] By adopting the above technical scheme, the present invention controls the water content to 4.5-5.5% to ensure fluidity while avoiding the loose structure caused by excessive moisture. Controlling the temperature and humidity maintenance (20-50°C, 80-100% RH) may promote the hydration reaction of the material to form a dense network structure, thereby enhancing the strength. In addition, the coordinated control of temperature and humidity can accelerate the early strength development and inhibit micro cracks caused by excessive temperature. The segmented heating heat treatment, wherein the initial insulation at 110-115°C (24-48h) first removes free water and residual stress, the insulation at 350°C in the medium temperature section (24-48h) can promote mineral phase transformation, and the insulation at 600°C in the high temperature section (16-32h) can strengthen grain boundary bonding. On this basis, segmented rate control is performed to avoid temperature mutations causing microscopic phase change stress, thereby helping to reduce internal stress and optimize grain structure.

[0026] In a third aspect, the present invention provides an application of the above-mentioned high-strength wear-resistant slide rail preform in a forging heating furnace slide rail.

[0027] In summary, the present invention has the following beneficial effects: 1. The present invention uses mullite (low expansion coefficient) of a specific particle size and alumina powder and alumina hollow balls (stress buffer) to synergistically reduce the risk of thermal stress cracking and improve the thermal shock resistance of the slide rail prefabricated parts; and then uses calcium aluminate cement and silicon micropowder to react at high temperature to form a continuous ceramic network. The slide rail prefabricated parts obtained in this way have excellent high-temperature strength, corrosion resistance and thermal shock resistance, and can significantly improve the service life of the slide rail.

[0028] 2. The alumina powder of the present invention uses large-particle 8-10µm trehalose composite α-alumina as the main skeleton, 4-6µm calcined alumina as the relay support, and finally 1-2µm activated alumina to fill the gap, thereby giving the slide rail prefabricated part better high temperature resistance, toughness and wear resistance; 3. The present invention adopts high humidity maintenance and coordinated temperature and humidity control to optimize the hydration structure of the material when preparing the slide rail prefabricated parts, and then uses step-by-step heating and segmented rate control to reduce internal defects and avoid temperature mutations that cause microscopic phase change stress, thereby ensuring the excellent high temperature strength, corrosion resistance and thermal shock resistance of the slide rail prefabricated parts. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0030] The raw materials of the present invention are all derived from conventional commercially available products, and the following need to be specially explained: Among the alumina powders, calcined alumina is used with a particle size of d 50 The activated alumina is a commercially available product with a particle size of 4-6 μm and a purity of ≥98.5%. 50 The commercially available product is 1-2μm, with a purity of ≥92% and a specific surface area of ​​≥500 m² / g; the α-alumina powder adopts a particle size of d 50 3-5μm, purity ≥95%, comparison area 3-5m 2 / g of commercially available products; trehalose used analytical standard products, HPLC ≥ 98%.

[0031] In addition, the alumina content of the aluminate cement used in the present invention is preferably 65-70%, and the calcium oxide content is 29-33%; the hollow alumina spheres preferably have a purity of ≥99%, a particle size of 0.2-0.5 mm, and a bulk density of 0.8-0.9 g / cm 3 ; The water reducing agent is preferably at least one of sodium tripolyphosphate, sodium hexametaphosphate and boric acid.

[0032] Preparation Example of Trehalose Composite α-Alumina Powder Preparation Example 1

[0033] α-alumina powder and trehalose solution were mixed to form a slurry, the weight ratio of α-alumina powder to trehalose was 3:1, and the solid content of the slurry was controlled to be 20%; the slurry was injected into a mold and vibrated to exhaust, and then placed in an environment with a humidity of 90% and a temperature of 35°C for curing for 36 hours. After demolding, it was placed at 120°C for low-temperature pre-sintering, and the moisture was removed and then ground to a particle size of d 50 The particle size of the composite alumina powder is 8-10 μm, and the composite alumina powder 1 is obtained. Preparation Example 2

[0034] α-alumina powder and trehalose solution were mixed to form a slurry, the weight ratio of α-alumina powder to trehalose was 3:1, and the solid content of the slurry was controlled to be 20%; the slurry was injected into a mold and vibrated to exhaust, and placed in an environment with a humidity of 80% and a temperature of 30°C for curing for 48 hours, and after demolding, it was placed at 100°C for low-temperature pre-sintering, and the moisture was removed and then ground to a particle size of d 50 The particle size of the composite alumina powder 2 is 8-10 μm. Preparation Example 3

[0035] The α-alumina powder and trehalose solution were mixed to form a slurry, the weight ratio of α-alumina powder to trehalose was 3:1, and the solid content of the slurry was controlled to be 20%; the slurry was injected into a mold and vibrated to exhaust, and placed in an environment with a humidity of 100% and a temperature of 40°C for curing for 24 hours, and after demolding, it was placed at 150°C for low-temperature pre-sintering, and the moisture was removed and then ground to a particle size of d 50The particle size of the composite alumina powder is 8-10 μm, and the composite alumina powder 3 is obtained. Preparation Example 4

[0036] α-alumina powder and trehalose solution were mixed to form a slurry, the weight ratio of α-alumina powder to trehalose was 3:1, and the solid content of the slurry was controlled to be 20%; the slurry was injected into a mold and vibrated to exhaust, and then placed in an environment with a humidity of 65% and a temperature of 35°C for curing for 36 hours. After demolding, it was placed at 120°C for low-temperature pre-sintering, and the moisture was removed and then ground to a particle size of d 50 The particle size of the composite alumina powder is 8-10 μm, and the composite alumina powder 4 is obtained. Preparation Example 5

[0037] α-alumina powder and trehalose solution were mixed to form a slurry, the weight ratio of α-alumina powder to trehalose was 3:1, and the solid content of the slurry was controlled to be 20%; the slurry was injected into a mold and vibrated to exhaust, and then placed in an environment with a humidity of 90% and a temperature of 35°C for curing for 36 hours. After demolding, it was pre-sintered at 180°C, and the moisture was removed and then ground to a particle size of d 50 The particle size of the composite alumina powder is 8-10 μm, and the composite alumina powder 5 is obtained. Preparation Example 6

[0038] The α-alumina powder and trehalose solution were mixed to form a slurry, the weight ratio of α-alumina powder to trehalose was 2:1, and the solid content of the slurry was controlled to be 20%; the slurry was injected into a mold and vibrated to exhaust, and then placed in an environment with a humidity of 90% and a temperature of 35°C for curing for 36 hours. After demolding, it was placed at 120°C for low-temperature pre-sintering, and the moisture was removed and then ground to a particle size of d 50 The particle size of the composite alumina powder is 8-10 μm, and the composite alumina powder 6 is obtained. Preparation Example 7

[0039] α-alumina powder and trehalose solution were mixed to form a slurry, the weight ratio of α-alumina powder to trehalose was 4:1, and the solid content of the slurry was controlled to be 20%; the slurry was injected into a mold and vibrated to exhaust, and then placed in an environment with a humidity of 90% and a temperature of 35°C for curing for 36 hours. After demolding, it was placed at 120°C for low-temperature pre-sintering, and the moisture was removed and then ground to a particle size of d 50 The particle size of the composite alumina powder is 8-10 μm, and the composite alumina powder 7 is obtained.

[0040] The present invention is further described in detail below with reference to Examples and Comparative Examples. Example Example 1

[0041] The method for preparing the high-strength wear-resistant slide rail prefabricated part of this embodiment comprises the following steps: Accurately weigh 800 g of mullite particles, 50 g of alumina powder, 30 g of calcium aluminate cement, 30 g of silica powder, 87 g of hollow alumina balls, and 3 g of water reducer for later use; Among them, mullite is composed of the following particle sizes, and the particle size and weight percentage of each particle size in mullite are: 5-8mm 20%, 3-5mm 35%, 1-3mm 25%, 0-1mm 20%; alumina powder is composed of particle size d 50 Calcined alumina powder with a particle size of 4-6µm 50 Activated alumina powder with a particle size of 1-2µm 50 The trehalose composite α-alumina powder (composite alumina powder 1) with a weight ratio of 4:6:90 is mixed; the aluminate cement adopts CA-70, in which the alumina content is 68% and the calcium oxide content is 30%; the purity of the alumina hollow sphere is ≥99%, the particle size is 0.2-0.5mm, and the bulk density is 0.85g / cm 3 ; The water reducing agent is sodium tripolyphosphate.

[0042] Add 5.0% water by weight of the total raw material components to the above raw materials, mix, stir and vibrate to form, cure at 40°C and 90% relative humidity for 25 hours, heat to 110°C at 15°C / h after demolding and keep warm for 36 hours, then heat to 350°C at 25°C / h and keep warm for 36 hours, finally heat to 600°C at 18°C / h and keep warm for 24 hours to obtain the above-mentioned slide rail preform. Embodiment 2-5

[0043] In Examples 2-5, based on the method of Example 1, the amounts of the raw material components were adjusted, as shown in Table 1 below.

[0044] Table 1 Raw material composition of Examples 1-5 (unit: g) Example 1 Example 2 Example 3 Example 4 Example 5 Mullite particles 800 395 640 800 900 Alumina powder 50 100 40 50 33 Calcium aluminate cement 30 100 24 50 33 Silica powder 30 100 24 50 33 Alumina Hollow Balls 87 300 269 47 0 Water reducing agent 3 5 3 3 1 Embodiment 6-8

[0045] In Example 6-8, the particle size of mullite is adjusted based on the method of Example 1. In Example 6, the mullite is composed of the following particle sizes, and the particle size of each particle size and the weight percentage of mullite are: 5-8mm10%, 3-5mm10%, 1-3mm10%, 0-1mm70%; in Example 7, the mullite is composed of the following particle sizes, and the particle size of each particle size and the weight percentage of mullite are: 5-8mm30%, 3-5mm40%, 1-3mm30%, 0-1mm0%; in Example 8, the mullite is composed of the following particle sizes, and the particle size of each particle size and the weight percentage of mullite are: 5-8mm25%, 3-5mm25%, 1-3mm25%, 0-1mm25%. Examples 9-11

[0046] In Examples 9-11, based on the method of Example 1, the composition of the alumina powder was adjusted.

[0047] Among them, the alumina powder in Example 9 is a mixture of calcined alumina powder, activated alumina powder and trehalose composite α-alumina powder (composite alumina powder 1) in a weight ratio of 1:3:96; the alumina powder in Example 10 is a mixture of calcined alumina powder, activated alumina powder and trehalose composite α-alumina powder (composite alumina powder 1) in a weight ratio of 6:9:85; the alumina powder in Example 11 is a mixture of calcined alumina powder, activated alumina powder and trehalose composite α-alumina powder (composite alumina powder 1) in a weight ratio of 1:1:1. Examples 12-17

[0048] In Examples 12-17, based on the method of Example 1, the trehalose composite α-alumina powder (composite alumina powder 1) in the alumina powder is replaced. In which, composite alumina powder 2 is used in Example 12, composite alumina powder 3 is used in Example 13, composite alumina powder 4 is used in Example 14, composite alumina powder 5 is used in Example 15, composite alumina powder 6 is used in Example 16, and composite alumina powder 7 is used in Example 17. Examples 18-19

[0049] In Examples 18-19, the aluminate cement is replaced based on the method of Example 1. The aluminate cement in Example 18 is specifically CA-50, in which the alumina content is 55% and the calcium oxide content is 38%; the aluminate cement in Example 19 is specifically CA-80, in which the alumina content is 75% and the calcium oxide content is 13%. Embodiment 20

[0050] Example 20 Based on the method of Example 1, the hollow alumina spheres are replaced with alumina spheres with a purity of ≥99%, a particle size of 1.0-1.5 mm, and a bulk density of 0.80 g / cm 3 . Examples 21-23

[0051] In Examples 21-23, based on the method of Example 1, the parameters of the preparation method of the high-strength wear-resistant slide rail preform are adjusted.

[0052] The adjustments in Example 21 are as follows: Add 4.5% of water to the raw materials, stir and vibrate to form, and cure at 20°C and 100% relative humidity for 30 hours. After demolding, heat the mixture to 115°C at 10°C / h and keep it warm for 24 hours. Heat the mixture to 350°C at 15°C / h and keep it warm for 24 hours. Finally, heat the mixture to 600°C at 15°C / h and keep it warm for 16 hours to obtain the above-mentioned slide rail preform.

[0053] The adjustments in Example 22 are as follows: Add 5.5% of water by weight of the total raw material components to the raw materials, mix, stir and vibrate to form, and cure at a temperature of 50°C and a relative humidity of 80% for 20 hours. After demolding, heat up to 110°C at 20°C / h and keep warm for 48 hours, then heat up to 350°C at 30°C / h and keep warm for 48 hours, and finally heat up to 600°C at 20°C / h and keep warm for 32 hours to obtain the above-mentioned slide rail preform.

[0054] The adjustments in Example 23 are as follows: Add 5.0% water by weight of the total raw material components to the above raw materials, mix, stir and vibrate to form, cure at 40°C and 90% relative humidity for 25 hours, heat to 350°C at 15°C / h after demolding, keep warm for 72 hours, finally heat to 600°C at 18°C / h, keep warm for 24 hours, and obtain the above slide rail preform. Comparative Example Comparative Example 1

[0055] In this comparative example, based on the method of Example 1, the particle size distribution of the mullite particles is adjusted, and specifically, mullite particles with a particle size of 3-5 mm are used. Comparative Example 2

[0056] In this comparative example, based on the method of Example 1, the particle size distribution of the mullite particles is adjusted, and specifically, mullite particles of two sizes, 5-8 mm and 1-3 mm, are used, and the weight ratio of the two sizes, 5-8 mm and 1-3 mm, is 1:1. Comparative Example 3

[0057] In this comparative example, based on the method of Example 1, all the alumina powder was replaced with alumina hollow spheres. Comparative Example 4

[0058] In this comparative example, based on the method of Example 1, the trehalose composite α-alumina powder was replaced with α-alumina powder. Comparative Example 5

[0059] In this comparative example, based on the method of Example 1, the trehalose composite α-alumina powder was replaced with an equal amount of trehalose and α-alumina powder simply mixed to form a mixed alumina powder. Comparative Examples 6-11

[0060] In Comparative Examples 6-11, based on the method of Example 1, the composition of the alumina powder was adjusted.

[0061] Among them, the alumina powder in Comparative Example 6 is all calcined alumina powder, the alumina powder in Comparative Example 7 is all activated alumina powder, and the alumina powder in Comparative Example 8 is all trehalose composite α-alumina powder (composite alumina powder 1), and the three particle sizes of the alumina powder in Comparative Examples 6-8 are as follows: 50 The weight ratios of 4-6µm, 1-2µm, and 8-10µm are all 4:6:90.

[0062] In addition, the aluminum oxide powder in Comparative Example 9 has a particle size of d 50 Calcined alumina powder with a particle size of 4-6µm 50 Calcined alumina powder with a particle size of 1-2µm and d 50 The trehalose composite α-alumina powder (composite alumina powder 1) with a particle size of 8-10 μm was mixed in a weight ratio of 4:6:90; the alumina powder in comparative example 10 was composed of a particle size of d 50 Activated alumina powder with a particle size of 4-6µm 50 Activated alumina powder with a particle size of 1-2µm 50 The trehalose composite α-alumina powder (composite alumina powder 1) with a particle size of 8-10 μm is mixed in a weight ratio of 4:6:90; the alumina powder in Comparative Example 11 is mixed with calcined alumina powder, activated alumina powder and trehalose composite α-alumina powder (composite alumina powder 1) in a weight ratio of 4:6:90, and the particle size of the three alumina powders is d 50 All are 4-6µm. Performance testing

[0063] The slide rail preforms prepared in the above-mentioned Examples 1-23 and Comparative Examples 1-11 were tested for high temperature strength, corrosion resistance and thermal shock resistance. The specific test results are shown in Table 2 below.

[0064] 1. High temperature strength test Referring to ASTM C133-24, the specific test conditions are as follows: the slide rail prefabricated parts are made into specimens with a size of Φ50×50mm, kept at 1400℃ for 2h, cooled to room temperature, and then tested for compressive strength (CCS) and flexural strength (MOR) according to the standard process, in MPa.

[0065] 2. Corrosion resistance test The specific test conditions are: make the slide rail prefabricated parts into 25mm×25mm×125mm specimens and immerse them in 80℃, 20% H2SO4 solution for 168 hours, and calculate the high-temperature mass loss rate (Δm≤1.5% is qualified) in %.

[0066] 3. Thermal shock resistance test Referring to GB / T 30873-2014, the slide rail prefabricated parts were made into specimens with a size of 25mm×25mm×150mm, and the surface was polished to Ra≤1.6μm. The temperature was raised to 1400℃ at a rate of 15℃ / min and kept warm for 30min. The specimens were quickly transferred to deionized water at room temperature (25±5℃) and completely immersed in it for 3min. After being taken out, they were dried in an oven at 110℃ for 1 hour and naturally cooled to room temperature. The above “heating-immersion-drying” was repeated 5 times, and the flexural strength (MOR) after 5 cycles was tested. The thermal shock strength retention rate (compared with the initial strength) was calculated in %.

[0067] Table 2 Test results of Examples 1-23 and Comparative Examples 1-11 CCS(MPa) MOR(MPa) High temperature mass loss rate (%) Thermal shock strength retention rate (%) Example 1 155 28 0.6 93.8 Example 2 127 20 0.9 87.7 Example 3 136 24 0.8 90.5 Example 4 140 25 0.7 91.0 Example 5 132 22 0.8 89.3 Example 6 131 22 0.8 90.2 Example 7 142 26 0.9 89.5 Example 8 147 27 0.7 91.6 Example 9 149 27 0.7 90.8 Example 10 144 26 0.7 89.7 Embodiment 11 131 22 0.8 88.5 Example 12 153 27 0.6 93.1 Embodiment 13 152 27 0.6 92.9 Embodiment 14 145 24 0.7 90.6 Embodiment 15 130 20 0.9 87.6 Example 16 149 26 0.9 91.7 Embodiment 17 142 23 0.7 90.3 Embodiment 18 134 21 0.6 89.9 Embodiment 19 146 24 1.0 91.0 Embodiment 20 141 23 0.7 90.2 Embodiment 21 150 27 0.6 92.2 Embodiment 22 151 27 0.6 92.4 Embodiment 23 127 19 1.0 86.3 Comparative Example 1 91 10 1.8 73.2 Comparative Example 2 100 12 1.7 76.6 Comparative Example 3 83 8 2.1 70.2 Comparative Example 4 101 12 1.7 76.4 Comparative Example 5 108 15 1.5 77.5 Comparative Example 6 107 14 1.6 77.0 Comparative Example 7 94 10 2.4 70.6 Comparative Example 8 113 16 1.3 80.1 Comparative Example 9 110 15 1.9 79.3 Comparative Example 10 102 12 1.7 76.5 Comparative Example 11 117 17 1.8 78.9 Combined with Table 2, by comparing the test results of Examples 1-23 with Comparative Examples 1-11, it can be obtained that the present invention uses mullite with four particle size ranges and alumina powder and alumina hollow spheres to synergistically reduce the risk of thermal stress cracking, and then uses calcium aluminate cement and silica powder to react at high temperature to form a continuous ceramic network. The slide rail preform obtained has strong compressive strength (CCS) and flexural strength (MOR), low high-temperature mass loss rate and high thermal shock strength retention rate, thus having excellent high-temperature strength, corrosion resistance and thermal shock resistance, and can significantly improve the service life of the slide rail. In addition, compared with the method of not adding trehalose (Comparative Example 4), adding trehalose alone (Comparative Example 5) and using a single or two alumina powders (Comparative Examples 6-11), the present invention needs to use a particle size of d 50 Calcined alumina powder with a particle size of 4-6µm 50 Activated alumina powder with a particle size of 1-2µm 50 The alumina powder mixed with 8-10µm trehalose composite α-alumina powder can effectively exert the performance of each component, and the slide rail preform obtained has excellent high temperature strength and thermal shock resistance.

[0068] By comparing the inspection results of Examples 1-5, it can be obtained that, in the present invention, as the amount of mullite increases, CCS and MOR show a trend of first increasing and then decreasing, the high-temperature mass loss rate continues to decrease, and the thermal shock strength retention first increases and then stabilizes. The addition of hollow alumina balls will slightly weaken the high-temperature mass loss rate and improve the thermal shock resistance to a certain extent. Combined with the adjustment of the components of alumina powder, calcium aluminate cement, silica powder and water reducer, the corresponding CCS, MOR, high-temperature mass loss rate and thermal shock strength retention rate will change accordingly. On the whole, the mullite solution of 64-80% is further preferred, among which Examples 1, 3 and 4 all have excellent effects.

[0069] By comparing the test results of Example 1 with those of Examples 6-8, it can be obtained that the particle size distribution of the mullite of the present invention will also affect the performance of the slide rail preform to a certain extent, wherein the mullite particles composed of four particle size distributions of 5-8mm 10-30%, 3-5mm 10-40%, 1-3mm 10-30%, and 0-1mm 0-70% are preferred, and the mullite particles composed of 5-8mm20%, 3-5mm 35%, 1-3mm 25%, and 0-1mm 20% are further preferred.

[0070] By comparing the test results of Example 1 with those of Examples 9-17, it can be seen that the alumina powders with different configurations in the present invention have a greater influence on the high temperature strength and thermal shock resistance of the slide rail preform. The present invention preferably uses a particle size of d 50 Calcined alumina powder with a particle size of 4-6µm 50 Activated alumina powder with a particle size of 1-2µm 50 Alumina powder is a mixture of 8-10µm trehalose-composite α-alumina powder in a weight ratio of 1-6:3-9:85-96. The trehalose-composite α-alumina is preferably obtained by the preparation method of "mixing α-alumina powder and trehalose solution to form slurry, injecting the slurry into a mold and vibrating and exhausting, curing for 24-48 hours in an environment with a humidity of 80-100% and a temperature of 30-40°C, and pre-calcining at 100-150°C after demoulding, and grinding after removing moisture", and the corresponding weight ratio of α-alumina powder to trehalose is 3:1.

[0071] By comparing the test results of Example 1 with those of Examples 18-20, it can be found that the different parameters of the aluminate cement and the hollow alumina balls in the present invention will also affect the overall performance of the slide rail prefabricated part to a certain extent. Therefore, the present invention further limits the alumina content in the aluminate cement to 65-70%, the calcium oxide content to 29-33%; the hollow alumina balls preferably have a purity of ≥99%, a particle size of 0.2-0.5 mm, and a bulk density of 0.8-0.9 g / cm 3 .

[0072] By comparing the test results of Example 1 with those of Examples 21-23, it can be concluded that the present invention adopts high humidity curing and coordinated control of temperature and humidity (20-50°C, 80-100% RH) to optimize the hydration structure of the material when preparing the slide rail prefabricated parts, and then utilizes step-by-step heating and segmented rate control (initial insulation at 110-115°C (24-48h) to first remove free water and residual stress, insulation at a medium temperature section at 350°C (24-48h) to promote mineral phase transformation, and insulation at a high temperature section at 600°C (16-32h) to strengthen grain boundary bonding) to reduce internal defects, thereby avoiding microscopic phase change stress caused by sudden temperature changes, thereby ensuring the excellent high temperature strength, corrosion resistance and thermal shock resistance of the slide rail prefabricated parts.

[0073] In summary, the high-strength wear-resistant slide rail preform produced in the present application has excellent high-temperature strength, corrosion resistance and thermal shock resistance, and can be well applied to forging heating furnace slide rails.

[0074] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A high-strength wear-resistant slide rail prefabricated component, characterized in that: The invention comprises the following raw material components by weight percentage: 39.5-90% of mullite particles, 3.3-10% of alumina powder, 2.4-10% of calcium aluminate cement, 2.4-10% of silica powder, 0-30% of alumina hollow spheres, and 0.1-0.5% of water reducing agent; The mullite is composed of the following particle sizes, and the particle size and weight percentage of each particle size in the mullite are: 5-8mm 10-30%; 3-5mm 10-40%; 1-3mm 10-30%; 0-1mm 0-70%; The alumina powder has a particle size of d 50 Calcined alumina powder with a particle size of 4-6µm 50 Activated alumina powder with a particle size of 1-2µm 50 It is a mixture of 8-10µm trehalose composite α-alumina powder.

2. The high-strength wear-resistant slide rail prefabricated component according to claim 1 is characterized in that: The weight ratio of the calcined alumina powder, the activated alumina powder and the trehalose composite alpha-alumina powder is 1-6:3-9:85-96.

3. The high-strength wear-resistant slide rail prefabricated component according to claim 1 is characterized in that: The preparation method of the trehalose composite α-alumina powder comprises the following steps: Mix α-alumina powder and trehalose solution to make slurry, inject the slurry into a mold, vibrate and exhaust, place it in an environment with a humidity of 80-100% and a temperature of 30-40°C for curing for 24-48 hours, and place it at 100-150°C for low-temperature pre-sintering after demoulding, remove moisture and then grind it.

4. The high-strength wear-resistant slide rail prefabricated component according to claim 3 is characterized in that: The weight ratio of the α-alumina powder to the trehalose is 3:

1.

5. The high-strength wear-resistant slide rail prefabricated component according to claim 1 is characterized in that: The alumina content of the aluminate cement is 65-70%, and the calcium oxide content is 29-33%.

6. The high-strength wear-resistant slide rail prefabricated component according to claim 1, characterized in that: The purity of the hollow alumina spheres is ≥99%, the particle size is 0.2-0.5 mm, and the bulk density is 0.8-0.9 g / cm 3 .

7. The high-strength wear-resistant slide rail prefabricated component according to claim 1 is characterized in that: The water reducing agent is at least one of sodium tripolyphosphate, sodium hexametaphosphate and boric acid.

8. A method for preparing a high-strength wear-resistant slide rail prefabricated component, characterized in that: The method for preparing the high-strength wear-resistant slide rail prefabricated component according to any one of claims 1 to 7 comprises the following steps: Take a set amount of raw material components, add 4.5-5.5% of water accounting for the total weight of the raw material components to mix, stir and vibrate to form, cure for 20-30 hours at a temperature of 20-50°C and a relative humidity of 80-100%, heat to 110-115°C at 10-20°C / h after demolding, keep warm for 24-48 hours, then heat to 350°C at 15-30°C / h, keep warm for 24-48 hours, finally heat to 600°C at 15-20°C / h, keep warm for 16-32 hours, and obtain the high-strength wear-resistant slide rail prefabricated component.

9. Use of the high-strength wear-resistant slide rail preform according to any one of claims 1 to 7 in forging heating furnace slide rails.

Citation Information

Patent Citations

  • High-thermal shock wear-resistant slide rail brick and preparation method thereof

    CN107840674A

  • Burning-free and soaking-free composite sliding plate brick for stopping slag of converter and preparation method of composite sliding plate brick

    CN114988855A

  • Low-heat-conductivity high-strength calcium hexaluminate castable for walking beam of heating furnace

    CN117285367A

  • Sintered zircon-mullite refractory composite, process for its production and its use

    DE102015119053A1

  • Carbon-containing refractory and its production

    JP1998212155A